2009
DOI: 10.2967/jnumed.108.058602
|View full text |Cite
|
Sign up to set email alerts
|

Pretargeted Versus Directly Targeted Radioimmunotherapy Combined with Anti-CD20 Antibody Consolidation Therapy of Non-Hodgkin Lymphoma

Abstract: We determined whether therapeutic responses using a bispecific antibody that pretargeted 90 Y-hapten-peptide radioimmunotherapy or a directly radiolabeled, humanized, 90 Y-anti-CD20 IgG (veltuzumab) could be improved by combining these treatments with unlabeled humanized antibodies against CD22 (epratuzumab), CD74 (milatuzumab), or veltuzumab. Methods: Nude mice bearing established subcutaneous Ramos human Burkitt lymphoma were treated with antibodies alone or in combination with pretargeted radioimmunotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 32 publications
1
45
0
Order By: Relevance
“…This possibility was suggested by recent experiments with Burkitt lymphoma-bearing nude mice, which showed that unlabeled antibodies against CD20 (veltuzumab) but not against CD22 (epratuzumab) or CD74 (milatuzumab) improved the therapeutic response achieved with 90 Y-hapten-peptide PRIT. 95 Benefits of such an approach may largely depend on exact experimental conditions, as indicated by the observation that tumor uptake was significantly reduced when unlabeled veltuzumab was administered in advance of the radiolabeled veltuzumab or bispecific antibody injection. Likewise, the net effect on PRIT efficacy, that is, improvement or worsening, depended on the amount of predosed unlabeled veltuzumab.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…This possibility was suggested by recent experiments with Burkitt lymphoma-bearing nude mice, which showed that unlabeled antibodies against CD20 (veltuzumab) but not against CD22 (epratuzumab) or CD74 (milatuzumab) improved the therapeutic response achieved with 90 Y-hapten-peptide PRIT. 95 Benefits of such an approach may largely depend on exact experimental conditions, as indicated by the observation that tumor uptake was significantly reduced when unlabeled veltuzumab was administered in advance of the radiolabeled veltuzumab or bispecific antibody injection. Likewise, the net effect on PRIT efficacy, that is, improvement or worsening, depended on the amount of predosed unlabeled veltuzumab.…”
Section: Figmentioning
confidence: 99%
“…Additional improvements may also come from the use of other novel strategies, such as the integration of unlabeled antibodies into PRIT-based therapies. 95 Undoubtedly, PRIT will remain an exciting avenue because of constant methodological refinements. With continued research, it holds the potential to establish itself as an important treatment modality for hematologic and other malignancies for smallvolume disease, as radiation boost in combination with other treatments such as stem-cell rescue, or as adjuvant therapy.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…26,27 The rationale behind this method was to saturate normal tissue sinks with naked antibody, thereby potentially decreasing off-target toxicity and allowing deeper ADC penetration into tumor tissues. Although there are merits to this approach and it is used for approved radioimmunotherapies, 28,29 only preclinical examples exist in the ADC space. Successful integration of this methodology in clinical ADC dosing will require careful titration of the naked antibody dose to the intact ADC dose; ratios may have to be patient specific to factor in disease burden and may be dependent on tumor type.…”
Section: Starting Dose and Dose-escalation Strategiesmentioning
confidence: 99%
“…The administration of 4 weekly doses of unlabeled anti-CD20 IgG starting 1 week after RIT with the same mAb enhanced the effect of RIT and improved survival compared with RIT alone and starting the administration of unlabeled anti-CD20 IgG before RIT. 24 Biodistribution data showed a lower tumor uptake of the radioimmunoconjugate when unlabeled anti-CD20 IgG was administered before RIT, which might explain the lower therapeutic effect. Hence, consolidation therapy with unlabeled mAbs after RIT might be effective; however, it will probably be less effective in patients given a high predose.…”
mentioning
confidence: 99%